Biodiversity Different and Species Assemblages of Phytoplankton Within Ooze Sediment at Myll Lakes, New South Wales Australia - Rukminasari, Nita (Jurnal Perikanan Universitas Gadjah Mada, 2009)
Phytoplanktons are primary producer, which determine the waters productivity. The assemblages of phytoplankton in the lake varied spatially and temporally as a result of nutrient concentration, some physical and chemical factors. However, the assemblage of phytoplankton in the lake was not well documented.  The overall aim of the study was  to count and identify phytoplankton taxa and to examine assemblages at location with and without ooze, and to relate the presence/absence of ooze to phytoplankton abundance and assemblages. The samples were collected from Myall Lakes, NSW Australia. The data were analysed using multivariate analysis to determine assemblages of phytoplankton amongst location. Furthermore, univariate analysis was used to examine how the water quality was in particular presence/absence of ooze affected to phytoplankton abundance. The hypothesis being tested was: (1) phytoplankton assemblages vary spatially in Myall Lake due to varying water quality characteristics, including presence of ooze, (2) there was a significant difference of phytoplankton abundances between locations due to presence/absence of ooze.In both instance the hypothesis on this study was accepted. There was a significant different not only phytoplankton assemblages but also phytoplankton abundance within locations. It concluded that the phytoplankton varied spatially in those locations. Presence/absence of ooze affects abundance of phytoplankton. However, further study was needed to conduct in particular to determine certain aspects which affect the assemblages and abundances of phytoplankton.